Decreased Bleeding Rates in Patients with Hemophilia A Switching from Standard-Half-Life FVIII to BAY 94-9027 Prophylaxis - Mancuso, Maria Elisa; Reding, Mark T.; Negrier, Claude; Kerlin, Bryce A.; Rangarajan, Savita; Simpson, Mindy L. (Thrombosis and Haemostasis, 2021)
BAY 94-9027 (damoctocog alfa pegol, Jivi) is an extended-half-life recombinant factor VIII (rFVIII) shown to be well-tolerated and efficacious in bleeding prevention in previously treated patients with severe hemophilia A. During the PROTECT VIII study, prophylaxis patients received BAY 94-9027 at intervals determined based on their bleeding phenotype, observed during a 10-week run-in treatment period with twice-weekly dosing. Those with ≤ 1 spontaneous joint or muscle bleed were randomized to either 45 to 60 IU/kg every 5 days or 60 IU/kg every 7 days; patients could increase dosing frequency to every 5 days or twice weekly in the case of bleeds. Those enrolled after the randomization arms were full, and those with ≥ 2 bleeds in the run-in period, received 30 to 40 IU/kg twice weekly. Patients completing the main study could receive open-label BAY 94-9027 in the extension phase. Dosing regimen, total, and joint annualized bleeding rates were analyzed over three periods: prestudy, main study, and extension. A total of 80 patients who were on prophylaxis treatment prior to and during the study and had prior bleed data available were evaluated in this post hoc analysis of PROTECT VIII. Most patients (> 80%) required fewer infusions with BAY 94-9027 prophylaxis versus their previous standard-half-life (SHL) rFVIII product. Lower bleeding and joint bleeding rates were observed over time from the prestudy to the extension study period in all treatment regimens. Compared with SHL FVIII, BAY 94-9027 prophylaxis allows patients to reduce infusion frequency with maintained or improved protection from bleeds.
Keywords: annualized bleeding rate; hemophilia A; prophylaxis; recombinant factor VIII; target joint